1990
DOI: 10.1021/bi00481a009
|View full text |Cite
|
Sign up to set email alerts
|

Carbon-13 NMR relaxation times of hepatic glycogen in vitro and in vivo

Abstract: The field dependence of relaxation times of the C-1 carbon of glycogen was studied in vitro by natural-abundance 13C NMR. T1 is strongly field dependent, while T2 does not change significantly with magnetic field. T1 and T2 were also measured for rat hepatic glycogen enriched with [1-13C]glucose in vivo at 4.7 T, and similar relaxation times were observed as those obtained in vitro at the same field. The in vitro values of T1 were 65 +/- 5 ms at 2.1 T, 142 +/- 10 ms at 4.7 T, and 300 +/- 10 ms at 8.4 T, while … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

9
112
0

Year Published

1992
1992
2018
2018

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 56 publications
(121 citation statements)
references
References 17 publications
9
112
0
Order By: Relevance
“…5 shows the nicely resolved natural abundance C 1 resonance of glycogen (100 ppm) before and after glucagon administration. Given that liver glycogen is known to be 100% visible by 13 C NMR (6,8), these data demonstrate that glycogen indeed disappears after exposure to glucagon and is essentially below the detection limits of 13 C NMR after Ϸ120 min. This result is in agreement with the changes in CEST described above.…”
Section: Resultsmentioning
confidence: 66%
See 1 more Smart Citation
“…5 shows the nicely resolved natural abundance C 1 resonance of glycogen (100 ppm) before and after glucagon administration. Given that liver glycogen is known to be 100% visible by 13 C NMR (6,8), these data demonstrate that glycogen indeed disappears after exposure to glucagon and is essentially below the detection limits of 13 C NMR after Ϸ120 min. This result is in agreement with the changes in CEST described above.…”
Section: Resultsmentioning
confidence: 66%
“…Because there are numerous practical disadvantages to measuring glycogen by tissue biopsy in humans, there has been widespread interest in detection of glycogen in vivo by 13 C magnetic resonance (MR) spectroscopy (MRS) in multiple organs, including the heart (2), liver (3), skeletal muscle (4), and brain (5). Although glycogen is a large molecule, 13 C NMR allows accurate measurements of glycogen content in liver (6) and in skeletal muscle (7), presumably because internal motions remain sufficiently unrestricted in vivo (8). Detection of glycogen using 1 H NMR also has been demonstrated (9)(10)(11).…”
mentioning
confidence: 99%
“…However, on one occasion we measured the saturation factor in vivo, which equaled that measured in solution within a few percent. The similarity in saturation factors is supported by the observation that TI of hepatic glycogen measured in vivo was within 10% of the in vitro T, (9). In addition, relaxation studies suggested that TI of glycogen is determined mostly by fast internal motions of the molecule (7, -lo-' s) and TI i s therefore less likely to be affected by the overall motion (9).…”
Section: Discussionmentioning
confidence: 65%
“…30 min, during which the signals remained stable within the signal-to-noise for all in vivo and in vitro experiments. In one study, we added a measurement with an increased repetition time of 476 ms, corresponding to approximately 3Tl (9). The ratio of this spectrum to that obtained with the standard TR of 176 ms indicated that the saturation factor (which includes effects of TI and NOE when measured as here) in vivo was within a few percent of that measured in phantom solutions, i.e., indistinguishable with the current signal-tonoise.…”
Section: Resultsmentioning
confidence: 88%
“…Due to high intramolecular mobility (20), C1-C6 resonances have been observed for I3C-labeled liver glycogen (14,21). However, in the I3C NMR spectra for the CEM cells, glycogen resonances were not detected.…”
Section: Discussionmentioning
confidence: 99%